2008
DOI: 10.1073/pnas.0808567105
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the gut microbiota on host adiposity are modulated by the short-chain fatty-acid binding G protein-coupled receptor, Gpr41

Abstract: The distal human intestine harbors trillions of microbes that allow us to extract calories from otherwise indigestible dietary polysaccharides. The products of polysaccharide fermentation include shortchain fatty acids that are ligands for Gpr41, a G protein-coupled receptor expressed by a subset of enteroendocrine cells in the gut epithelium. To examine the contribution of Gpr41 to energy balance, we compared Gpr41؊/؊ and Gpr41؉/؉ mice that were either conventionally-raised with a complete gut microbiota or w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
1,037
8
15

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,359 publications
(1,109 citation statements)
references
References 23 publications
21
1,037
8
15
Order By: Relevance
“…Recently, the ability of the intestinal microbiome to regulate liver inflammation was established and was due in part on the ability of bacterial components in the portal blood (7). A similar effect of gut microbiome on adiposity has been demonstrated via the G protein-coupled receptor Gpr41 (28). This established that bacterial components can enter the portal circulation and regulate liver inflammation.…”
Section: G738mentioning
confidence: 88%
“…Recently, the ability of the intestinal microbiome to regulate liver inflammation was established and was due in part on the ability of bacterial components in the portal blood (7). A similar effect of gut microbiome on adiposity has been demonstrated via the G protein-coupled receptor Gpr41 (28). This established that bacterial components can enter the portal circulation and regulate liver inflammation.…”
Section: G738mentioning
confidence: 88%
“…GPR41 is another SCFA receptor. Binding to GPR41 is associated with upregulation of peptide YY (PYY) and glucagon-like peptide 1 [(GLP1), anorectic hormones] that have effects on appetite control; therefore, SCFAs are linked to food intake by activating these receptors (78,79). Current evidence indicates that SCFAs have paradoxical effects on hepatic health.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that GI microbiota is host-specific and GI tract region-specific (Zoetendal et al, 2004;Rajilic-Stojanovic et al, 2009;Jalanka-Tuovinen et al, 2011), aberrant in composition and stability in patients suffering from GI disorders such as Crohn's disease (Seksik et al, 2003), and associated to host energy homeostasis (Backhed et al, 2004;Ley et al, 2006;Turnbaugh et al, 2006;Backhed et al, 2007;Samuel et al, 2008). Analysis of global fecal microbiomes introduced the concept that human GI microbiota appeared to have three distinct structural biometypes called enterotypes (Arumugam et al, 2011).…”
Section: Introductionmentioning
confidence: 99%